CO2 storage in saline aquifers II-Experience from existing storage operations - Michael, K.; Allinson, G.; Golab, A.; Sharma, S.; Shulakova, Valeriya (2009)
The Intergovernmental Panel of Climate Change Special Report on Carbon Capture and Storage in 2005 identified various knowledge gaps that need to be resolved before the large-scale implementation of CO2 geological storage is possible. The experience from CO2 injection at pilot projects (Frio, Ketzin, Nagaoka) and existing commercial operations (Sleipner, Snøhvit, In Salah, acid-gas injection) demonstrates that CO2 geological storage in saline aquifers is technologically feasible. By the end of 2007, approximately 15 Mt of CO2 had been successfully injected into saline aquifers by these operations. However, these projects are not necessarily representative of conditions encountered globally. A larger portfolio of large-scale storage operations is needed to provide data for verification and calibration of numerical models, to better constrain geomechanical as well as geochemical processes, and to optimize monitoring and verification plans for different storage settings. © 2009 Elsevier Ltd. All rights reserved.